QEEG markers of superior shooting performance in skilled marksmen: An investigation of cortical activity on psychomotor efficiency hypothesis. (March 2023) - Cheng, Ming-Yang; Wang, Kuo-Pin; Doppelmayr, Michael; Steinberg, Fabian; Hung, Tsung-Min; Lu, Calvin; Tan, Ying Ying; Hatfield, Bradley
Abstract: For elite performers, psychomotor behavior's success or failure can be traced to differences in brain dynamics. The psychomotor efficiency hypothesis suggests refined cortical activity through 1) selective activation of task-relevant processes and 2) inhibition of non-essential processes. The use of electroencephalography (EEG) has been applied to investigate psychomotor performance's neural processes. The EEG markers that reflect an elevation of psychomotor efficiency include left temporal alpha (T3 alpha), frontal midline theta (Fm theta), sensorimotor rhythm (SMR), and the coherence between frontal and left temporal regions. However, the relationship between elite performers' task-relevant and non-essential neural processes is still not well understood. Therefore, this study aimed to explore how each task-relevant and inhibition of non-essential processes contribute to superior psychomotor behavior. Thirty-five highly skilled marksmen were recruited to perform 30 shots in the shooting task while the EEG was recorded. The marksmen were divided into two groups (superior & inferior) based on a median split of shooting performance. The superior group exhibited higher accuracy and precision, with a reduction in movement jerk. EEG measures revealed that the superior group exhibited higher SMR before the trigger pull than the inferior group. In addition, the superior group demonstrated reduced Fz-T3 coherence in their bull's eye shots than the missed shots. These results suggest that the superior group exhibited less effortful engagement of task-relevant processes and lower interference from non-essential cortical regions than the inferior group. The study's overall findings support the psychomotor efficiency hypothesis. When comparing highly skilled performers, the slight differences in brain dynamics ultimately contribute to the success or failure of psychomotor performance. Highlights: Superior shooting performance is typified by the higher sensorimotor rhythm (SMR) power during the aiming period. Adaptive allocation of task-specific attention separates the optimal shots from the off-target shots. Sensorimotor rhythm and the Fz-T3 alpha coherence may represent the psychomotor efficiency.